Look at Me: Early Gaze Engagement Enhances Corticospinal Excitability During Action Observation - Betti, Sonia; Zani, Giovanni; Granziol, Umberto; Guerra, Silvia; Castiello, Umberto; Sartori, Luisa (Frontiers in Psychology, 2018)
Direct gaze is a powerful social cue able to capture the onlooker’s attention. Beside gaze, head and limb movements as well can provide relevant sources of information for social interaction. This study investigated the joint role of direct gaze and hand gestures on the onlooker corticospinal excitability (CE). In two experiments we manipulated the temporal and the spatial aspects of observed gaze and hand behavior to assess their role in affecting motor preparation. To do this, transcranial magnetic stimulation (TMS) on the primary motor cortex (M1) coupled with electromyography (EMG) recording was used in two experiments. In the crucial manipulation, we showed to participants four video clips of an actor who initially displayed eye contact while starting a social request gesture (Step 1), and then completed the action (Step 2) while directing his gaze toward a salient object for the interaction. This way, observed gaze potentially expressed the intention to interact. Eye tracking data confirmed that gaze manipulation was effective in drawing observers’ attention to the actor’s hand gesture. In the attempt to reveal possible time-locked modulations, we tracked CE across both the action steps. Neurophysiological results showed a significant CE modulation only during the first step, when the actor was about to start the request gesture looking straight to the participants, compared to when his gaze was averted from the gesture. This effect was time-locked to the kinematics of the actor’s arm movement. Overall, data from the two experiments seem to indicate that the joint contribution of direct gaze and precocious kinematic information gained while a request gesture is on the verge of beginning increases the subjective experience of involvement and allows observers to prepare for an appropriate social interaction. On the contrary, the separation of gaze cues and body kinematics can have adverse effects on social interaction. CE is highly susceptible to biological cues such as averted gaze, which is able to automatically capture and divert observer’s attention. This points to the existence of heuristics based on early action and gaze cues that would allow observers to interact appropriately.